Saxophone, Stylistic Orientations and Directions in Tableaux de Provence – J. M. Paule Maurice - Bogdan CONSTANTIN; Doru ALBU (Studia Universitatis Babeş-Bolyai. Musica)
Considered a reference work in the musical literature dedicated to the saxophone, the Tableaux de Provence suite for saxophone and orchestra was composed between 1954 – 1959 with dedication to a saxophonist virtuoso, but also family friend – Marcel Mule. The programmatic vision is evident from the suggestive titles, suitable for each image. The contrast is a specific feature of the suite genre, being approached by composers at the thematic level as well as developed in all language elements. The purpose of this article is to decipher the interpretative stylistic – features of the Tableaux de Provence suite, which will lead to a better understanding of the style proposed by J. M. P. Maurice’s.